Astrocyte-derived exosomal miR-378a-5p mitigates cerebral ischemic neuroinflammation by modulating NLRP3-mediated pyroptosis - Sun, Ruiting; Liao, Wenxin; Lang, Ting; Qin, Keyi; Jiao, Keyan; Shao, Le; Deng, Changqing; She, Yan (Frontiers in Immunology, 2024)
Objective: This study aimed to investigate the regulatory role of astrocyte-derived exosomes and their microRNAs (miRNAs) in modulating neuronal pyroptosis during cerebral ischemia.Methods: Astrocyte-derived exosomes were studied for treating cerebral ischemia in both in vitro and in vivo models. The effects of astrocyte-derived exosomes on neuroinflammation were investigated by analyzing exosome uptake, nerve damage, and pyroptosis protein expression. High throughput sequencing was used to identify astrocyte-derived exosomal miRNAs linked to pyroptosis, followed by validation via qRT-PCR. The relationship between these miRNAs and NLRP3 was studied using a dual luciferase reporter assay. This study used miR-378a-5p overexpression and knockdown to manipulate OGD injury in nerve cells. The impact of astrocyte-derived exosomal miR-378a-5p on the regulation of cerebral ischemic neuroinflammation was assessed through analysis of nerve injury and pyroptosis-related protein expression.Our findings demonstrated that astrocyte-derived exosomes were internalized by neurons both in vitro and in vivo. Additionally, Astrocyte-derived exosomes displayed a neuroprotective effect against OGD-induced neuronal injury and brain injury in the ischemic cortical region of middle cerebral artery occlusion (MCAO) rats while also reducing pyroptosis. Further investigations revealed the involvement of astrocyte-derived exosomal miR-378a-5p in regulating pyroptosis by inhibiting NLRP3. The overexpression of miR-378a-5p mitigated neuronal damage, whereas the knockdown of miR-378a-5p increased NLRP3 expression and exacerbated pyroptosis, thus reversing this neuroprotective effect.Astrocyte-derived exosomal miR-378a-5p has a neuroprotective effect on cerebral ischemia by suppressing neuroinflammation associated with NLRP3-mediated pyroptosis.Further research is required to comprehensively elucidate the signaling pathways by which astrocyte-derived exosomal miR-378a-5p modulates neuronal pyroptosis.